A STUDY OF CONSUMER BEHAVIOUR IN PURCHASING FOODSTUFFS: A CASE STUDY OF SOFIA, BULGARIA - Borislav ATANASOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Traditionally, foodstuffs are included in the consumer basket of households. Statistics for recent years reveals an upward trend in the marketof fast-moving consumer goods in Bulgaria. The growth in the number of retail outlets and in the number of fast-moving consumer goods in articular poses challenges to retail chains. The entry of foreign chains for consumer goods on the Bulgarian market as well as the variety oftheir product and brand supply result in intensified competition between them. The desire for increased market share is a prerequisite to roviding higher value to end consumers through the elements of a commercial product which ensure competitive advantages. In order to stablish the key (motivational) factors in the purchase process related to foodstuffs, a questionnaire was developed and a quantitative urvey was conducted based on the method of the structured personal interview. The survey also shows the frequency of purchasing various roups of foodstuffs, the degree of purchase planning, the impact of reference groups on the purchasing process through one-dimensional requency distributions.